The Effect of Interval Training on Running Speed 100 meters for grade VII students of SMP Negeri 1 Sedati - Chikito Wahyu Ramadhan; Luqmanul Hakim (Green Publisher Indonesia, 2026)
This research is motivated by the low 100-meter sprint speed of seventh-grade students at SMP Negeri 1 Sedati and the lack of variation in training methods provided. The objective of this study is to determine the significant effect of implementing the interval training method on improving students' 100-meter sprint speed. This study adopts a quantitative approach with a quasi-experimental method using a Pretest-Posttest Control Group Design. The research population consisted of all seventh-grade students at SMP Negeri 1 Sedati, with a sample of 30 students selected through a purposive sampling technique. The instrument used was a 100-meter sprint test to measure student speed before and after the treatment. Data analysis was conducted using the Independent Samples T-Test facilitated by SPSS software. The results showed a significant difference between the experimental group and the control group. Based on the statistical analysis, a significance value (2-tailed) of 0.000 was obtained, which is lower than the 0.05 significance level (0.000<0.05 0.000<0.05). The average speed improvement in the experimental group was significantly higher than in the control group, which received conventional instruction. In conclusion, the interval training method has a significant positive influence on increasing 100-meter sprint speed. This study suggests that physical education teachers should implement interval training as an effective variation to enhance students' athletic abilities.